2021
DOI: 10.1088/1742-6596/1858/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Herbal Hand Sanitizer Based on Stevia (Stevia rebaudiana)

Abstract: The purpose of this study was to analyze the quality of herbal hand sanitizer based on stevia in the addition of trembesi (Albizia saman (Jacq.) Merr) leaf extract. Experimental research in the laboratory, the study used two factorial Completely Randomized Design, namely stevia extract (1.0; 0.75; 0.50; 0.25; 0.0%) and trembesi extract (0; 0.25;0, 5;0.75; 1.0%) with two repetitions. Each formulation was tested according to SNI 0625881992. The results showed that all formulation comply with SNI-06-2588-1992 sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Antimicrobial activity of polyherbal hand sanitizer [18] The antimicrobial activity of the polyherbal hand sanitizer was evaluated using the agar well diffusion method against various microorganisms. The results showed that the formulation exhibited significant antimicrobial activity against all the tested microorganisms [Table 8].…”
Section: Physical Chemical and Microbiological Stability Of Formulationmentioning
confidence: 99%
“…Antimicrobial activity of polyherbal hand sanitizer [18] The antimicrobial activity of the polyherbal hand sanitizer was evaluated using the agar well diffusion method against various microorganisms. The results showed that the formulation exhibited significant antimicrobial activity against all the tested microorganisms [Table 8].…”
Section: Physical Chemical and Microbiological Stability Of Formulationmentioning
confidence: 99%
“…Furthermore, the extract of temu hitam rhizome was dissolved in distilled water and stirred until dissolved. The soluble temu hitam rhizome extract is put into a mortar and ground homogeneously until a gel is formed [22], [23].…”
Section: Formulation Of Hand Sanitizer Gel Preparation Of Temu Hitam ...mentioning
confidence: 99%
“…The first use of stevia-based compounds was in food industries, but they are also considered to be therapeutic agents nowadays [7]. Accordingly, several types of investigations in all in silico, in vitro, in vivo, and clinical media have been carried out on stevia to recognize there featured activities [8][9][10][11]. Besides such therapeutic importance, a general demand has been arisen on use of stevia as a natural product in everyday life style package [12].…”
Section: Introductionmentioning
confidence: 99%